DOP008 Safety of adalimumab in children and adolescents with moderate-to-severe Crohn's disease: interim results of the CAPE registry. (16th January 2018) - Turner, D; Koletzko, S; Winter, H; Baldassano, R; Dubinsky, M; Faubion, W; Hyams, J; Kugathasan, S; Rosh, J; Escher, J; Griffiths, A; Kierkus, J; et al.
Abstract: Background: The 3-year safety and efficacy data of adalimumab (ADA) in children and adolescents with moderately to severely active Crohn's disease (CD) enrolled in the IMAgINE 1 trial ( N = 192; ADA exposure, 151.8 patient-years [PYs]) were previously reported (Faubion, et al. IBD 2017). ADA long-term safety and effectiveness is currently being assessed in the postmarketing observational registry, CAPE. Interim safety data are reported herein. Methods: CAPE is a non-interventional, multinational, registry designed to include up to 10 years of routine clinical practice data on paediatric patients (6–17 years) with moderately to severely active CD receiving ADA (Humira®) or immunomodulator (IMM) monotherapy (azathioprine, mercaptopurine, or methotrexate). For this interim analysis at 3 years (started August 29, 2014), adverse events (AEs) were monitored through May 31, 2017. AE rates were assessed as events per 100 PYs (E/100 PYs) of ADA and IMM exposure, respectively. Registry treatment-emergent AEs (TEAEs) were defined as any AE occurring from the first dose of ADA or IMM in the registry through the last dose plus 70 days (ADA) or 30 days (IMM) or up to cut-off. Results: A total of 909 patients (ADA, N = 518; IMM, N = 391) were enrolled representing 378.8 and 328.2 PYs of exposure to ADA and IMM, respectively. 28 patients have withdrawn from the registry (ADA, n = 13; IMM, n = 15). At entry into CAPE, patient median (interquartile range) age was 15 (13–16) years and mean (SD) CD duration was 2.8 (2.46) years; the majority of patients are male (59%) and white (89%). TEAE incidence proportions and event rates per 100 PYs are shown in Table 1. The rates of AEs and serious AEs (SAEs) were lower than the rates reported in the IMAgINE clinical trials. The majority of SAEs were associated with underlying CD in both registry groups. The most common serious infection ( n [%]) was abdominal abscess in the ADA registry group (3 [0.6]) and gastroenteritis in the IMM registry group (2 [0.5]). There were no TEAEs of opportunistic infection, tuberculosis, malignancy, or demyelinating disorders reported in either registry group. Three cases of worsening/new onset of psoriasis were reported in the ADA group. No pregnancies or deaths were reported. Conclusions: The safety of ADA observed in CAPE was comparable to its known benefit risk profile in children and adolescents with moderately to severely active CD, and no new safety signals were identified. Longer observation periods are needed to ascertain a more accurate risk of uncommon AEs.